(3bUI ecJHI (B:s (3NeShf YGeG aj UMHI GdcJH hGdecJHGJ aj GdhWf GdYQHj hNGQLg (B/s - (3YSjdGf, YHO Gddg YHO GdQMjes 1945- ((3GdQjGV (B- (3GdSYhOjI(B:s (3OGQ GdKdhKjI,s, 2017)
(3jYQV dfG GdeDda aj cJGHg gPG bUI Jchjf ecJHJg GdJj jYJR HgG hHeG JMJhjg ef faGFS GdcJH hGdeNWhWGJ GdeUhQI aj TJi Ufha GdYde hGdeYQaI, hHeG ajgG ef OhQjGJ COHjI hdZhjI, hCTQWI hSjOjgGJ ddYOjO ef GdeMGVQGJ hGdfOhGJ(B. (3MjK JbOQ eMJhjGJgG HeG jRjO Yf NeSI BdGa cJGH, cGf dgG GdaVd aj eSjQJg GdYdejI, hbO GSJZQb aj JchjfgG eG jRjO Ydi NeSjf YGeG(B.s
Keywords: (3GdecJHGJ s -- (3GdSYhOjIs -- (3GdNGUIs; (3GdcJH GdfGOQIs -- (3GdSYhOjIs